Use of WhatsApp to monitor proper brace application and compliance in a case of clubfoot: a feasibility report - Dharmshaktu, Ganesh Singh (International Journal of Research in Orthopaedics, 2018)
Internet provides immense potential to learn, indulge and implement several aspects of knowledge related activities for professionals and general enthusiasts alike. Emergence of social medial platforms, in the current scenario, has exponentially increased the reach of the data and thus its potential impact. WhatsApp is one of the leading media platforms to share views and news to a connected group and is widely used for its simple interface and ease of application. Its varied usage has benefitted biomedical and healthcare settings as well. We hereby describe feasibility of its use in home monitoring of brace application in a case of clubfoot by collaborating with parents. This turns out to be an exciting tool for this purpose in selected cases.